Linearization of Double Balanced Mixer Operated in Subthreshold Region of MOSFET - Sonika GUPTA; G RATHER; Najeeb Ud Din HAKİM (International Journal of Applied Methods in Electronics and Computers, 2015)
A mixer is an essential part of a communication system. It is generally used in wireless receiver to perform the translation from Radio Frequency (RF) to the intermediate frequency (IF). A non-linear device like Metal Oxide Semiconductor Field Effect Transistor (MOSFET) can be suitably used for mixing operation. In these devices, power consumption is a matter of concern because devices are continuously being scaled, but the power supply is not scaled correspondingly. In portable devices, it is important to save battery lifetime. So, it is required that the performance of mixers should be enhanced while considering power concerns also. When MOSFETs are operated in subthreshold region, there is lower power dissipation, and it has also been observed that in this region, drain current is exponential of input voltage. This nonlinearity can be used for mixing. But, this non-linearity should not be so large so as to cause distortion at the output of mixer. The distortion behavior of mixer is a matter of concern. This paper describes the results of applying linearization techniques to double balanced mixer while operating it in subthreshold region. 0.5 µm NMOS devices have been used to design mixer. Mixer has been designed for Bluetooth specifications.